A Planned and Coordinated Anarchy: The Barricades of 1971 and the “Diliman Commune” - Scalice, Joseph; University (Archīum Ateneo, 2019)
In early February 1971, students at UP Diliman erected barricades, fought off the military, and briefly established the “Diliman Commune.” Using material produced by the “communards” themselves, along with contemporary press reports, I reconstruct the dramatic narrative of the commune and debunk two prominent myths: that it was a spontaneous uprising and that it was an isolated event. The commune was a part of a widely coordinated set of barricades raised by the radical groups Kabataang Makabayan (KM) and Samahan ng Demokratikong Kabataan (SDK) in service, in the final analysis, to the political interests of their ruling class allies in an election year.KEYWORDS: DILIMAN COMMUNE • UNIVERSITY OF THE PHILIPPINES • ANARCHISM • STALINISM • MARCOS PRESIDENCY